An introduction to Akkadian literature: contexts and content - Lenzi, Alan (Penn State University Press, 2021)
Frontmatter -- Contents -- List of Illustrations -- Acknowledgments -- Abbreviations -- Prologue -- Introduction -- Akkadian: Linguistic, Geographical, and Chronological Parameters -- An Overview of the Textual Record -- Chapter 1. Prolegomena to the Study of Akkadian Literature -- Introduction -- Tablets: From Excavation to Translation -- Scribes: Contextualizing Literary Production -- Compositions: General Issues -- Audiences: Who Read These Texts? -- Chapter 2. Survey of Selected Text Groups -- Introduction -- Mythological and Heroic Epics -- Legends of Akkadian Kings -- Historiographical Texts -- Legal and Political Documents -- Divination: Deductive and Intuitive -- Other Scholarly Texts -- Prayers, Incantations, Incantation- Prayers, Laments, and Hymns -- Meditations on Human Suffering and the Divine -- Proverbs, Advice, Dialogues, and Debates -- Satire, Parody, and Humor -- Conclusion: The Future of Akkadian Literature -- Bibliography -- Index